2023
DOI: 10.1038/s41746-023-00911-x
|View full text |Cite
|
Sign up to set email alerts
|

Deep representation learning identifies associations between physical activity and sleep patterns during pregnancy and prematurity

Neal G. Ravindra,
Camilo Espinosa,
Eloïse Berson
et al.

Abstract: Preterm birth (PTB) is the leading cause of infant mortality globally. Research has focused on developing predictive models for PTB without prioritizing cost-effective interventions. Physical activity and sleep present unique opportunities for interventions in low- and middle-income populations (LMICs). However, objective measurement of physical activity and sleep remains challenging and self-reported metrics suffer from low-resolution and accuracy. In this study, we use physical activity data collected using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
(57 reference statements)
0
5
1
1
Order By: Relevance
“…55 Among these outputs, temperature provided the greatest contribution to the model. Although we were not able to find recent other recent studies of human temperature in labor prediction, 52 a research group recently 68 demonstrated decreases in physical activity with advancing gestational age, and an 18-participant cohort study demonstrated decreases in HR and increases in HRV in the third trimester. 69 Although more human studies are needed, these results build on a wealth of animal literature demonstrating unique decreases in temperature prior to parturition, and numerous efforts to identify features indicative of imminent labor, ranging from simple thresholds 43 to machine learning approaches similar to the present study.…”
Section: Discussioncontrasting
confidence: 74%
“…55 Among these outputs, temperature provided the greatest contribution to the model. Although we were not able to find recent other recent studies of human temperature in labor prediction, 52 a research group recently 68 demonstrated decreases in physical activity with advancing gestational age, and an 18-participant cohort study demonstrated decreases in HR and increases in HRV in the third trimester. 69 Although more human studies are needed, these results build on a wealth of animal literature demonstrating unique decreases in temperature prior to parturition, and numerous efforts to identify features indicative of imminent labor, ranging from simple thresholds 43 to machine learning approaches similar to the present study.…”
Section: Discussioncontrasting
confidence: 74%
“…26 Although less is known about the magnitude of perinatal risk, sleep disturbances in pregnancy have been associated with gestational diabetes, hypertensive disorders, preterm birth, and mental health conditions. 2,8,10,27–29 Whether the decrease in sleep that we identified contributes to worsening clinical status remains unknown.…”
Section: Discussionmentioning
confidence: 98%
“…4,6,7 Information about sleep and sleep quality is particularly important given the known associations between sleep disturbances and increases in complications such as gestational diabetes, hypertensive disorders, and preterm birth. 8–10 Therefore, we conducted a prospective pilot study to evaluate whether antepartum hospitalization was associated with differences in sleep duration and quality compared with gestational age–matched outpatients.…”
mentioning
confidence: 99%
“…Gleiches gilt auch für das Zulassen des weiblichen Orgasmus [21,19,9]. Eine aktuelle Studie der Universität Stanford [18] untersuchte den Zusammenhang zwischen erholsamem Schlaf sowie körperlicher Aktivität und dem Risiko, eine Frühgeburt zu erleiden. Die Ergebnisse zeigen signifikante Zusammenhänge zwischen einem erhöhten Frühgeburtsrisiko durch gestörten Schlafrhythmus und mangelnder körperlicher Aktivität.…”
Section: Der Einfluss Von Sexualität Auf Die Dauer Einer Schwangerschaftunclassified